In vitro activity of spice extracts against Arcobacter Spp. and influence on their biofilm formation - Šilha, David; Vacková, Barbora; Csánová, Magdaléna; Šilhová, Lucie (My University, 2019)
Arcobacter spp. are dangerous bacteria with biofilm formation ability. The plant materials with antimicrobial potential are required. The antimicrobial effect of several plant extracts were examined by a disk diffusion method. The effect of extracts on biofilm formation was monitored using Christensen method. Tests were carried out with much less known and studied arcobacters as well. Arcobacters were highly resistant to extracts from juniper, nutmeg and anise. Minimum inhibitory concentrations (MIC) of MetOH/DMSO (extraction in methanol/final dissolution in dimethylsulfoxide) of cloves, nutmeg and star anise extract were determined after 24 hours of exposure. The clove MetOH/DMSO extract had a MIC≥20 mg/mL, nutmeg MetOH/DMSO extract had MIC 10-20 mg/mL, and the highest values were recorded in star anise extract (MIC≥20 mg/mL). Furthermore, the tested extracts were found to have a dual effect on biofilm formation. On the one hand, the elimination of biofilm formation was observed, but also its stimulation, depending on the type of extract and the bacterial strain. The results indicate a particularly interesting antimicrobial effect of cloves and cinnamon extract (inhibition zones up to 30 mm) against Arcobacter strains. The study shows a promising effect of tested extracts on biofilm formation for the first time.
In vitro aktivita extraktů koření proti Arcobacter spp. a vliv na tvorbu biofilmu
Keywords: Arcobacter spp.; biofilm; biofilm formation; natural extracts; biofilm inhibition; Arcobacter spp.; biofilm; tvorba biofilmu; přírodní extrakty; inhibice biofilmové tvorby